2018
DOI: 10.1038/s41389-018-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel series of Nitroxoline-derived BET inhibitors with antitumor activity in renal cell carcinoma

Abstract: Small molecular inhibitors targeting BRD4 family proteins are emerging as promising therapies in many types of human malignancies. However, whether BRD4, as well as other BET family members, may serve as therapeutic targets in renal cell carcinoma (RCC) remains unknown. In this study, we found that both BRD2 and BRD4 were over-expressed in RCC tissues, knock-down both of which achieved potent anti-proliferative effects in RCC cells. A novel category of BET inhibitors, originated from an approved drug Nitroxoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In that study, nitroxoline was found to affect viability, to drastically reduce clonogenic activity, to hamper cell cycle and to promote apoptosis in pancreatic cancer cell lines, both as a single agent and in combinations with other drugs 7 . In addition to pancreatic cancer, this drug affects viability and growth of cell lines representative of other tumors, including neuroblastoma, glioma, myeloma, prostate, lung, kidney and bladder cancers [8][9][10][11][12][13][14][15][16][17][18][19] . Remarkably, this antibiotic is also effective in several cancer xenograft and genetically engineered mice models [8][9][10]12,14,15,18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, nitroxoline was found to affect viability, to drastically reduce clonogenic activity, to hamper cell cycle and to promote apoptosis in pancreatic cancer cell lines, both as a single agent and in combinations with other drugs 7 . In addition to pancreatic cancer, this drug affects viability and growth of cell lines representative of other tumors, including neuroblastoma, glioma, myeloma, prostate, lung, kidney and bladder cancers [8][9][10][11][12][13][14][15][16][17][18][19] . Remarkably, this antibiotic is also effective in several cancer xenograft and genetically engineered mice models [8][9][10]12,14,15,18 .…”
mentioning
confidence: 99%
“…Nitroxoline is an antibiotic widely used in several countries from 1960s and is able to chelate divalent metal ions such as Mg 2+ and Mn 2+ , an activity which is considered as a possible mechanism for its antibacterial action 3 . To analyze mechanisms by which this antibacterial exerts its anticancer activity, several studies screened for specific candidate targets and molecular pathways known to play an important role in cancer biology [7][8][9][10][11][12][13][14][15][16][17][18][19] . Using this approach, disparate targets have been proposed to be responsible for nitroxoline anticancer effects.…”
mentioning
confidence: 99%
“…The compound was, therefore, evaluated further for its antitumor activity (Sosič et al, 2013;Mitrović et al, 2017). It showed higher activity than did nitroxoline for inhibition of tumor cell invasion and migration in vitro on cell lines in both two-dimensional and three dimensional models as well as in in vivo on tumor mice model compound 17 showed improved inhibition of (Sosič et al, 2013), compound 48 (Bhat et al, 2012) and compound BDF-1253 (Chen et al, 2018).…”
Section: Nitroxoline Derivativesmentioning
confidence: 99%
“…In addition a novel series of nitroxoline derivatives with improved potency of inhibition of BET proteins and that bound competitively to the BRD4-BD1, were prepared (Chen et al, 2018;Xing et al, 2019). Structural modifications of nitroxoline derivatives effective as BET inhibitors (Chen et al, 2018;Xing et al, 2019) differed from those reported for cathepsin B inhibition (Mirković et al, 2011;Sosič et al, 2013Sosič et al, , 2018Mitrović et al, 2017). Preparation of the first nitroxoline derivatives for BET inhibition showed that, here, introduction of additional hydroxyl group to the nitroxoline ring had a favorable effect.…”
Section: Nitroxoline Derivativesmentioning
confidence: 99%
See 1 more Smart Citation